2021
DOI: 10.1002/cjp2.205
|View full text |Cite
|
Sign up to set email alerts
|

A distinct repertoire of cancer‐associated fibroblasts is enriched in cribriform prostate cancer

Abstract: Outcomes for men with localized prostate cancer vary widely, with some men effectively managed without treatment on active surveillance, while other men rapidly progress to metastatic disease despite curative-intent therapies. One of the strongest prognostic indicators of outcome is grade groups based on the Gleason grading system. Gleason grade 4 prostate cancer with cribriform morphology is associated with adverse outcomes and can be utilized clinically to improve risk stratification. The underpinnings of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…However, vascular infiltration patterns and other stromal cells associated with ICC/IDC have not been robustly assessed. A recent study comparing cribriform morphology to other Gleason pattern 4 histologic subtypes, as well as lower Gleason patterns, showed that FAP + ASPN + cancer-associated fibroblasts (CAF) were enriched in regions directly adjacent to cribriform foci 33 . FAP has immunosuppressive functions in the TME 34,35 , yet little has been reported on the immune microenvironment associated with prostate ICC/IDC.…”
mentioning
confidence: 99%
“…However, vascular infiltration patterns and other stromal cells associated with ICC/IDC have not been robustly assessed. A recent study comparing cribriform morphology to other Gleason pattern 4 histologic subtypes, as well as lower Gleason patterns, showed that FAP + ASPN + cancer-associated fibroblasts (CAF) were enriched in regions directly adjacent to cribriform foci 33 . FAP has immunosuppressive functions in the TME 34,35 , yet little has been reported on the immune microenvironment associated with prostate ICC/IDC.…”
mentioning
confidence: 99%
“…For example, ACTA2 also serves as a general marker for vascular muscle cells and pericytes. Thus, the selective expression patterns of these markers could be used to characterize the phenotypic heterogeneity and functional diversity of activated CAFs within the specific TME (7,(34)(35)(36)(37)(38). Furthermore, the combination of these markers may enhance the differentiation of CAF subgroups, and different CAF subgroups have specific prognostic significance and exert different roles in efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This feature leads us to hypothesize that, similar to IDC, tumor cells find a safe haven within cribriform structures, away from the potentially harmful effects of the stroma. In addition, hypoxia that is higher within cribriform formations [75], probably as a result of the limited contact of the cells to the vessel-containing stroma [81], and the effects of a specific type of tumor-associated fibroblast found around cribriform structures that is distinct from fibroblasts associated with other morphologic patterns [82], may account for the aggressive behavior of cribriform-patterned carcinoma.…”
Section: Invasive Acinar Carcinoma With Cribriform Patternmentioning
confidence: 99%